'Closer to the Market': EU Research Governance and Symbolic Power. (18th February 2022) - Gengnagel, Vincent; Zimmermann, Katharina; Büttner, Sebastian M.
Abstract: Adding to vital debates in EU Studies about the executive power of European governance, this article analyses the influence of EU research funding in the social sciences. The standardization and enforcement of norms, principles, and language codes, we argue, play a crucial role in EU governance. Applying a mixed‐method approach, we show that mastery of the 'EU language game' does more than help scholars obtain EU funding; it also generates individual and disciplinary frictions, since it requires a subtle re‐orientation of social‐scientific research towards political goals. Our study sheds light on strategies used by scientists who find themselves enmeshed in this language game, from euphoric adaptation to reluctant lip service. Since these academic strategies play out in the relative autonomy of liberal EU governance, the explicit focus on market integration is accompanied by a less explicit interest in matters of political representation and identity formation.